University Curriculum Development and Management Based on Korean National Competency Standards: A Case Study - Kim, Kyeong-eon; Kim, Juri; Yoon, Gwansik; Woo, & Heajung (Journal of Technical Education and Training, 2019)
Recently, the Korean government has been making various policy efforts to resolve the mismatch college education reflecting industry needs. Among them, the National Competency Standards (NCS) that sought to systematize the knowledge, skills, and attitudes required to perform jobs at different levels were developed. To date, NCS is leading to a shift in the curriculum of high schools, colleges, and public and private vocational training institutions. The K University was the first university to develop and manage an NCS based curriculum. This study analyses the cases of NCS based curriculum development and management of K university in Korea through cases study method. As a result of this study, K university developed NCS based curriculum at nine levels and managed systematically by introducing plan, do & check, Act. This means that K university has increased its efforts to better reflect the needs of the industry in the curriculum. By benchmarking the case of The K University’s NCS based curriculum development and management process, this study explores the possibility of applying NCS to college education, providing guidance and implications for overseas universities hoping to develop and introduce NCS based curriculum.